2023
DOI: 10.1002/ange.202305569
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Copper(I) Complexes for Near‐Infrared Light‐Emitting Electrochemical Cells

Abdelaziz Jouaiti,
Lavinia Ballerini,
Hsiang‐Ling Shen
et al.

Abstract: Two binuclear heteroleptic CuI complexes, namely Cu−NIR1 and Cu−NIR2, bearing rigid chelating diphosphines and π‐conjugated 2,5‐di(pyridin‐2‐yl)thiazolo[5,4‐d]thiazole as the bis‐bidentate ligand are presented. The proposed dinuclearization strategy yields a large bathochromic shift of the emission when compared to the mononuclear counterparts (M1–M2) and enables shifting luminescence into the near‐infrared (NIR) region in both solution and solid state, showing emission maximum at ca. 750 and 712 nm, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The results indicated that this metal-organic framework could generate high temperatures under near-infrared light irradiation and effectively kill brain tumor cells. This study provides a new option for photothermal therapy of brain tumors (Jouaiti et al, 2023). Additionally, a photothermal π-conjugated nanomaterial with excellent optical properties and investigated its application in brain tumor treatment.…”
Section: Photothermal Therapy and Photodynamic Therapymentioning
confidence: 99%
“…The results indicated that this metal-organic framework could generate high temperatures under near-infrared light irradiation and effectively kill brain tumor cells. This study provides a new option for photothermal therapy of brain tumors (Jouaiti et al, 2023). Additionally, a photothermal π-conjugated nanomaterial with excellent optical properties and investigated its application in brain tumor treatment.…”
Section: Photothermal Therapy and Photodynamic Therapymentioning
confidence: 99%